Not as widespread as thought: Integrative taxonomy reveals cryptic diversity in the Amazonian nurse frog Allobates tinae Melo-Sampaio, Oliveira and Prates, 2018 and description of a new species - Lima, Albertina Pimental; Ferrão, Miquéias; Lacerda da Silva, Douglas (Journal of Zoological Systematics and Evolutionary Research, 2020)
The small size, low vagility, territoriality, and reproductive mode of some Amazonian frogs undermine the wide geographical distribution assigned to them. Species with these features represent excellent models for testing the existence of cryptic diversity in widely distributed species. The nurse frog Allobates tinae has recently been described as widely distributed, occurring in various forest types, as well as on both banks of large rivers. Herein, we gather molecular, morphological, bioacoustics, and egg coloration data in order to investigate whether A. tinae actually represents a species complex. The sampling effort focuses on ~1,000 km of landscapes in the Purus–Madeira Interfluve (IPM), where two different forest types predominate. We use barcoding algorithm, cluster analysis, and machine learning to test the specific status currently assigned to A. tinae. Results were congruent in showing that the two lineages of A. tinae occurring in the IPM represent two different species, which can be distinguished from each other by adult morphology, larvae, advertisement call, and molecular data. The species inhabiting open ombrophilous forests in the southern IPM represents A. tinae sensu stricto, while the species that inhabits dense ombrophilous forests in the northern IPM represents a new species. We describe this new species and use egg coloration for the first time in the recent taxonomy of Allobates as a diagnostic feature. Additionally, we discuss the importance of egg characteristics on the taxonomy of Allobates and possible ecological reasons for differences observed in the egg melanin ratio between A. tinae sensu stricto and the new species. © 2020 Blackwell Verlag GmbH
Keywords: Amazonia; Bioacoustics; egg coloration; interfluve purus; Madeira; Morphology; Tadpoles